Battery negative electrode material and preparation method thereof

By forming a multi-layer clad structure on the silicon-based negative electrode material, the problem of low cycle life caused by volume expansion during lithiation and deliquency of the silicon-based negative electrode material is solved, and the high cycle stability and rate performance of the battery are achieved.

CN119674045AActive Publication Date: 2025-03-21SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD

Patent Information

Application Number
CN202510182453.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-21
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have a low cycle life due to volume expansion during lithiation and deliquification.

Method used

A battery negative electrode material adopts a multi-layer clad structure, including a silicon-based negative electrode material core, is coated with four layers of titanium dioxide, lithium titanate, carbon and polymer.

Benefits of technology

Through the synergy of the four-layer cladding layer, the volume expansion of the silicon-based negative electrode material during the lithiation and deliquency process is alleviated, structural stability and conductivity are enhanced, the cycle life of the battery is extended, and the rate performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674045A_ABST
    Figure CN119674045A_ABST
Patent Text Reader

Abstract

The invention discloses a battery negative electrode material and a preparation method thereof, and relates to the technical field of batteries. The battery negative electrode material comprises an inner core, a titanium dioxide coating layer coated on the surface of the inner core, a lithium titanate coating layer coated on the surface of the titanium dioxide coating layer, a carbon coating layer coated on the surface of the lithium titanate coating layer and a polymer coating layer coated on the surface of the carbon coating layer, the inner core comprises a silicon-based negative electrode material; the polymer coating layer comprises at least one of polyaniline, polythiophene and polypyrrole. Under the action of the four coating layers, the integrity of the silicon-based negative electrode material can be kept, direct contact between the silicon-based negative electrode material and an electrolyte is avoided, side reactions are reduced, the capacity fading of the battery in the charge-discharge cycle process is reduced, and the rate capability and the cycle stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery negative electrode material and a preparation method thereof. Background Art

[0002] At present, the theoretical specific capacity of graphite-based negative electrode materials is relatively low (372 mAh g -1 ) can no longer meet the needs of high energy density battery systems. Silicon-based negative electrode materials have high specific capacity and low delithiation potential (for example, the theoretical specific capacity of Si is 3579mAh·g -1 , the delithiation potential is about 0.4V vs. Li|Li + ), is an attractive alternative to commercial graphite anode materials in lithium-ion batteries. However, silicon-based anode materials undergo huge volume expansion during lithiation and delithiation, resulting in irreversible changes in particle morphology and size, continuous destruction and growth of the solid electrolyte interface (SEI) film, continuous consumption of active lithium, powderization of the pole piece, increased resistance and polarization, and reduced battery capacity and cycle life.

[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0004] Based on the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a battery negative electrode material and a preparation method thereof, aiming to solve the problem that the cycle life of batteries based on silicon-based negative electrode materials is low due to the volume expansion of existing silicon-based negative electrode materials during lithiation and delithiation.

[0005] The technical solution of the present invention is as follows: In a first aspect of the present invention, a battery negative electrode material is provided, wherein the battery negative electrode material comprises a core, and a titanium dioxide coating layer coated on the surface of the core, a lithium titanate coating layer coated on the surface of the titanium dioxide coating layer, a carbon coating layer coated on the surface of the lithium titanate coating layer, and a polymer coating layer coated on the surface of the carbon coating layer; The core includes a silicon-based negative electrode material; the polymer coating layer includes at least one of polyaniline, polythiophene and polypyrrole.

[0006] Optionally, the silicon-based negative electrode material includes at least one of a silicon negative electrode material, a silicon-oxygen negative electrode material and a silicon-carbon negative electrode material.

[0007] Optionally, the particle size of the silicon-based negative electrode material is 0.1-50 μm; The thickness of the titanium dioxide coating layer is 2-18 nm; the thickness of the lithium titanate coating layer is 2-10 nm; the thickness of the carbon coating layer is 5-10 nm; and the thickness of the polymer coating layer is 2-8 nm.

[0008] In a second aspect, the present invention provides a method for preparing the negative electrode material of the battery as described above, comprising the following steps: Provide silicon-based negative electrode materials; forming a titanium dioxide coating layer on the surface of the silicon-based negative electrode material, and forming a lithium titanate coating layer on the surface of the titanium dioxide coating layer to obtain a first composite; forming a carbon coating layer on the surface of the first composite to obtain a second composite; A polymer coating layer is formed on the surface of the second composite to obtain a battery negative electrode material.

[0009] Optionally, the step of forming a titanium dioxide coating layer on the surface of the silicon-based negative electrode material, and forming a lithium titanate coating layer on the surface of the titanium dioxide coating layer to obtain the first composite specifically includes: The liquid phase coating method is used to coat titanium dioxide on the surface of the silicon-based negative electrode material; A silicon-based negative electrode material coated with titanium dioxide on the surface is mixed with a lithium source and kept at 500-700° C. for 3-5 hours in an inert atmosphere, so that a titanium dioxide coating layer and a lithium titanate coating layer are sequentially formed on the surface of the silicon-based negative electrode material to obtain a first composite.

[0010] Optionally, the step of coating titanium dioxide on the surface of the silicon-based negative electrode material by a liquid phase coating method specifically includes: The silicon-based negative electrode material is added into a first solvent, and then a titanium source and water are added, so that titanium dioxide is coated on the surface of the silicon-based negative electrode material through a hydrolysis reaction.

[0011] Optionally, the titanium source includes at least one of titanium tetrachloride, tetrabutyl titanate, titanium isopropoxide, titanium sulfate, titanyl sulfate and titanium trichloride; The lithium source includes at least one of lithium nitrate, lithium acetate, lithium phosphate, lithium sulfate, lithium chloride, lithium bromide and lithium iodide.

[0012] Optionally, the step of forming a carbon coating layer on the surface of the first composite to obtain the second composite specifically includes: The first composite is mixed with a carbon source, and heated at 500-700° C. for 2-3 hours under an inert gas atmosphere to form a carbon coating layer on the surface of the first composite, thereby obtaining a second composite.

[0013] Optionally, the carbon source includes at least one of tetrahydrofuran, asphalt, acetone, citric acid and phenolic resin.

[0014] Optionally, the step of forming a polymer coating layer on the surface of the second composite to obtain a negative electrode material for a battery specifically includes: Adding the second complex, polymer monomers, coupling agent and initiator into the second solvent, and after reaction, forming a polymer coating layer on the surface of the second complex to obtain a negative electrode material for a battery; The polymer monomer includes at least one of aniline, thiophene and pyrrole.

[0015] Beneficial effects: The titanium dioxide coating layer in the present invention has a certain rigidity, which can buffer the volume expansion of silicon-based negative electrode materials during lithiation and delithiation, reduce the mechanical stress of silicon-based negative electrode materials, and enhance structural stability. The lithium titanate coating layer can serve as a lithium ion conductive layer to enhance the transmission of lithium ions. It can also serve as an artificial SEI film to avoid the natural generation of SEI film during the cycle. On the one hand, the carbon coating layer can enhance the conductivity of silicon-based negative electrode materials, and on the other hand, it also has a certain buffering effect on the volume expansion of silicon-based negative electrode materials. The polymer coating layer has good toughness and conductivity, which can effectively alleviate the volume expansion of silicon-based negative electrode materials and prevent the silicon-based negative electrode materials from breaking. In addition, it can not only serve as an intermediate isolation layer between the active material (i.e., silicon-based negative electrode material) and the electrolyte, reduce the occurrence of side reactions, and be more friendly to the electrolyte, but also promote interface ion diffusion, thereby ensuring the smooth embedding and de-embedding of lithium ions. Under the action of these four coating layers, the integrity of the silicon-based negative electrode material can be maintained, avoiding direct contact between the silicon-based negative electrode material and the electrolyte, reducing the occurrence of side reactions, reducing the capacity attenuation of the battery during the charge and discharge cycle, and improving the battery's rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the structure of the battery negative electrode material.

[0017] Figure 2 This is the X-ray diffraction pattern of the negative electrode material of the battery in Example 1.

[0018] Figure 3 This is the X-ray photoelectron spectrum of the negative electrode material of the battery in Example 2, where (a) is the characteristic peak of SiO2 and Si, and (b) is the characteristic peak of TiO2.

[0019] Figure 4 This is the energy spectrum of the battery negative electrode material in Example 3.

[0020] Figure 5 Graph showing the cycle test results of lithium-ion batteries prepared using the battery negative electrode materials in Example 1 and Comparative Example 1.

[0021] Figure 6 Graph showing the cycle test results of lithium-ion batteries prepared using the battery negative electrode materials in Example 2 and Comparative Example 2.

[0022] Figure 7Graph showing the cycle test results of lithium-ion batteries prepared using the battery negative electrode materials in Example 3 and Comparative Example 3.

[0023] Figure 8 This is a graph showing the cycle test results of lithium-ion batteries prepared using the battery negative electrode materials in Example 1, Example 2, Example 3 and Comparative Example 4.

[0024] Fig. 9 This is a graph showing the rate test results of lithium-ion batteries prepared using the battery negative electrode materials in Example 1 and Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0025] Fig.10 Impedance diagrams of lithium-ion batteries prepared using the battery negative electrode materials in Example 2 and Comparative Example 1 after 0.5 and 50.5 cycles, wherein (a) is the impedance diagram after 0.5 cycles, and (b) is the impedance diagram after 50.5 cycles. DETAILED DESCRIPTION

[0026] The present invention provides a battery negative electrode material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0027] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0028] If there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.

[0029] An embodiment of the present invention provides a battery negative electrode material, wherein: Figure 1 As shown, the battery negative electrode material has a core-shell structure, specifically, the battery negative electrode material includes a core 1, and a titanium dioxide coating layer 2 coated on the surface of the core 1, a lithium titanate coating layer 3 coated on the surface of the titanium dioxide coating layer 2, a carbon coating layer 4 coated on the surface of the lithium titanate coating layer 3, and a polymer coating layer 5 coated on the surface of the carbon coating layer 4; The core includes a silicon-based negative electrode material; the polymer coating layer includes at least one of polyaniline, polythiophene and polypyrrole.

[0030] The titanium dioxide coating layer in the present invention has a certain rigidity, which can buffer the volume expansion of the silicon-based negative electrode material during the lithiation process, reduce the mechanical stress of the silicon-based negative electrode material, and enhance the structural stability. The lithium titanate coating layer can be used as a lithium ion conductive layer to enhance the transmission of lithium ions. It can also act as an artificial SEI film to avoid the natural generation of the SEI film during the cycle. On the one hand, the carbon coating layer can enhance the conductivity of the silicon-based negative electrode material, and on the other hand, it also has a certain buffering effect on the volume expansion of the silicon-based negative electrode material. The polymer coating layer has good toughness and conductivity, which can effectively alleviate the volume expansion of the silicon-based negative electrode material and prevent the silicon-based negative electrode material from breaking. In addition, it can not only act as an intermediate isolation layer between the active material (i.e., the silicon-based negative electrode material) and the electrolyte, reduce the occurrence of side reactions, and be more friendly to the electrolyte, but also promote interface ion diffusion, thereby ensuring the smooth embedding and de-embedding of lithium ions. Under the action of these four coating layers, the integrity of the silicon-based negative electrode material can be maintained, avoiding direct contact between the silicon-based negative electrode material and the electrolyte, reducing the occurrence of side reactions, reducing the capacity attenuation of the battery during the charge and discharge cycle, and improving the battery's rate performance and cycle stability.

[0031] In some embodiments, the silicon-based negative electrode material includes at least one of a silicon negative electrode material (such as nano silicon particles, micro silicon particles, nano silicon wires, etc.), a silicon oxygen negative electrode material, and a silicon carbon negative electrode material, but is not limited thereto. The silicon negative electrode material, the silicon oxygen negative electrode material, and the silicon carbon negative electrode material can all be commercially available products obtained through commercial channels.

[0032] In some embodiments, the particle size of the silicon-based negative electrode material is 0.1~50μm, for example, it can be 0.1μm, 0.5μm, 1μm, 2μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm, etc.

[0033] In some embodiments, the thickness of the titanium dioxide coating layer is 2-18 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm or 18 nm, etc. Such a thickness can effectively buffer the volume expansion of the silicon-based negative electrode material during the charge and discharge process. If it is too thick, it will cause excessive resistance to lithium ion insertion and affect the electrochemical performance.

[0034] In some embodiments, the thickness of the lithium titanate coating layer is 2-10 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, etc. The lithium titanate coating layer of this thickness can better enhance the transmission of lithium ions, act as an artificial SEI film, and avoid the natural formation of SEI film during the cycle process.

[0035] In some embodiments, the thickness of the carbon coating layer is 5-10 nm, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, etc. If the carbon coating layer is too thin, it is easy to be incompletely coated, resulting in poor conductivity, and if the coating is too thick, the side reaction will be aggravated, resulting in a reduced battery life.

[0036] In some embodiments, the thickness of the polymer coating layer is 2-8 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm or 8 nm, etc. The polymer coating layer of such thickness has the following functions: it can provide an additional conductive path to improve the overall conductivity of the battery negative electrode material; it can protect the internal silicon-based negative electrode material and each coating layer; it has good adhesion, which can better make the polymer coating layer contact with the carbon coating layer; it can reduce the contact resistance between the coating materials and reduce energy loss; it has good flexibility and mechanical properties to prevent the silicon-based negative electrode material particles from breaking.

[0037] The present invention also provides a method for preparing the negative electrode material of the battery as described above, which comprises the following steps: S1. Provide silicon-based negative electrode materials; S2, forming a titanium dioxide coating layer on the surface of the silicon-based negative electrode material, and forming a lithium titanate coating layer on the surface of the titanium dioxide coating layer to obtain a first composite; the first composite comprises a silicon-based negative electrode material, a titanium dioxide coating layer coated on the surface of the silicon-based negative electrode material, and a lithium titanate coating layer coated on the surface of the titanium dioxide coating layer; S3, forming a carbon coating layer on the surface of the first composite to obtain a second composite; the second composite comprises a silicon-based negative electrode material, a titanium dioxide coating layer coated on the surface of the silicon-based negative electrode material, a lithium titanate coating layer coated on the surface of the titanium dioxide coating layer, and a carbon coating layer coated on the surface of the lithium titanate coating layer; S4. Forming a polymer coating layer on the surface of the second composite to obtain a battery negative electrode material.

[0038] The preparation method provided by the present invention is simple, has low equipment requirements, has no pollution in the reaction process, has good product uniformity, and the prepared battery negative electrode material has high specific capacity, good cycle and rate performance, and safety. In step S1, the selection of silicon-based negative electrode materials can be referred to the above description and will not be repeated here.

[0039] In step S2, in some embodiments, a titanium dioxide coating layer is formed on the surface of the silicon-based negative electrode material, and a lithium titanate coating layer is formed on the surface of the titanium dioxide coating layer to obtain a first composite, specifically comprising: S21, coating titanium dioxide on the surface of the silicon-based negative electrode material by a liquid phase coating method; S22. Mix the silicon-based negative electrode material with titanium dioxide coated on the surface with a lithium source, and keep it at 500-700° C. for 3-5 hours in an inert atmosphere, so that a titanium dioxide coating layer and a lithium titanate coating layer are sequentially formed on the surface of the silicon-based negative electrode material to obtain a first composite.

[0040] In this embodiment, a layer of titanium dioxide can be uniformly coated on the surface of the silicon-based negative electrode material by a liquid phase coating method, and then the surface layer of the titanium dioxide layer is lithiated into lithium titanate by a lithium source at a temperature of 500~700°C to form a lithium titanate coating layer, and the titanium dioxide layer that is not lithiated constitutes the titanium dioxide coating layer.

[0041] In step S21, in some embodiments, the step of coating titanium dioxide on the surface of the silicon-based negative electrode material by a liquid phase coating method specifically includes: The silicon-based negative electrode material is added into a first solvent, and then a titanium source and water are added, so that titanium dioxide is coated on the surface of the silicon-based negative electrode material through a hydrolysis reaction.

[0042] The first solvent includes at least one of ethanol, ethylene glycol and methanol, but is not limited thereto. The titanium source includes at least one of titanium tetrachloride, tetrabutyl titanate, titanium isopropoxide, titanium sulfate, titanyl sulfate and titanium trichloride, but is not limited thereto.

[0043] In step S21, in some embodiments, the mass ratio of the titanium source to the silicon-based negative electrode material is (0.001~0.05):1, for example, it can be 0.001:1, 0.002:1, 0.005:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1 or 0.05:1, etc.

[0044] In step S21 and step S22, in some embodiments, the mass ratio of the lithium source to the silicon-based negative electrode material is (0.005~0.05):1, for example, it can be 0.005:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1 or 0.05:1, etc.

[0045] In step S22, in some embodiments, the lithium source includes at least one of lithium nitrate, lithium acetate, lithium phosphate, lithium sulfate, lithium chloride, lithium bromide and lithium iodide, but is not limited thereto.

[0046] In some embodiments, a silicon-based negative electrode material coated with titanium dioxide is mixed with a lithium source, heated and stirred in an 80° C. water bath for 12 to 24 hours, dried, and kept at 500 to 700° C. in an inert atmosphere for 3 to 5 hours to obtain a first composite.

[0047] In step S3, in some embodiments, the step of forming a carbon coating layer on the surface of the first composite to obtain the second composite specifically includes: The first composite is mixed with a carbon source, and heated at 500-700° C. for 2-3 hours under an inert gas atmosphere to form a carbon coating layer on the surface of the first composite, thereby obtaining a second composite.

[0048] In some embodiments, the mass ratio of the carbon source to the silicon-based negative electrode material in the first composite is (20-80):1, for example, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1 or 80:1.

[0049] In some embodiments, the carbon source includes at least one of tetrahydrofuran, asphalt, acetone, citric acid, and phenolic resin, but is not limited thereto.

[0050] In step S4, in some embodiments, the step of forming a polymer coating layer on the surface of the second composite to obtain a negative electrode material for a battery specifically includes: Adding the second complex, polymer monomers, coupling agent and initiator into the second solvent, and after reaction, forming a polymer coating layer on the surface of the second complex to obtain a negative electrode material for a battery; The polymer monomer includes at least one of aniline, thiophene and pyrrole.

[0051] In some embodiments, the mass ratio of the second complex, polymer monomer, coupling agent and initiator is 1: (0.05~0.5): (0.01~0.3): (0.01~0.2), for example, it can be 1:0.05:0.01:0.01, 1:0.1:0.01:0.01, 1:0.5:0.01:0.01, 1:0.05:0.3:0.01, 1:0.05:0.01:0.1 or 1:0.05:0.01:0.2, etc.

[0052] In some embodiments, the coupling agent includes a silane coupling agent (for example, the silane coupling agent includes at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, aminoethylaminopropyltrimethoxysilane and 3-(2-aminoethylamino)propyltrimethoxysilane), the initiator includes at least one of ammonium persulfate, sodium persulfate and potassium persulfate, and the second solvent includes at least one of ethanol, ethylene glycol and methanol.

[0053] The present invention will be further described below by means of specific examples.

[0054] Unless otherwise specified, the materials used in the following examples and comparative examples are all commercially available products. Among them, the silicon-oxygen negative electrode materials used in the following examples and comparative examples are all from Shenzhen Solid New Material Technology Co., Ltd., and the product name is SH-1490 (particle size is 1~50μm).

[0055] Example 1 This embodiment provides a method for preparing a negative electrode material for a battery, comprising the following steps: (1) 10 g of silicon oxide negative electrode material was dispersed in 400 mL of anhydrous ethanol, and 0.3 g of tetrabutyl titanate and 20 mL of deionized water were added. After stirring for 20 min, the tetrabutyl titanate was hydrolyzed to generate titanium dioxide coated on the surface of the silicon oxide negative electrode material; then 10 mL of lithium nitrate solution (containing 0.1 g of lithium nitrate) was added, and after mixing evenly, the mixture was heated and stirred in a water bath at 80° C. for 20 h. After drying, the mixture was heated to 700° C. in a nitrogen atmosphere and kept warm for 3 h to convert the surface layer of titanium dioxide into lithium titanate, thereby obtaining a first composite (which includes a silicon oxide negative electrode material and a titanium dioxide coating layer coated on the surface of the silicon oxide negative electrode material, and a lithium titanate coating layer coated on the surface of the titanium dioxide coating layer).

[0056] (2) 10 g of the first composite was added to 200 g of tetrahydrofuran, stirred, and dried at 100 °C. The mixture was then placed in a horizontal tube furnace and heated to 600 °C at a heating rate of 5 °C / min under an argon gas flow, and heated at 600 °C for 2 h to form a carbon coating layer on the surface of the first composite, thereby obtaining a second composite.

[0057] (3) 10 g of the second complex was added to 200 mL of anhydrous ethanol and magnetically stirred for 10 minutes. At a temperature of 80°C, 0.5 g of 3-aminopropyltrimethoxysilane was added. After reacting for 1.5 hours, 2 mL of aniline was added and stirred to obtain a mixed solution A. 0.3 g of ammonium persulfate was dissolved in 10 mL of deionized water to obtain an ammonium persulfate solution. The obtained ammonium persulfate solution was slowly added dropwise to the mixed solution A through a separatory funnel and reacted for 3 hours. After the reaction was completed, the mixture was repeatedly washed with deionized water and ethanol and filtered twice, and then placed in a vacuum environment at 100°C until completely dried to obtain a battery negative electrode material. The battery negative electrode material includes a silicon oxide negative electrode material core, and titanium dioxide coating layer (thickness of 10 nm), lithium titanate coating layer (thickness of 3 nm), carbon coating layer (thickness of 5 nm) and polyaniline coating layer (thickness of 4 nm) sequentially coated on the surface of the silicon oxide negative electrode material core from the inside to the outside.

[0058] Example 2 This embodiment provides a method for preparing a negative electrode material for a battery, which is different from Embodiment 1 only in that in step (1), 0.05 g of tetrabutyl titanate is added.

[0059] The obtained battery negative electrode material includes a silicon oxygen negative electrode material core, and a titanium dioxide coating layer (2nm thick), a lithium titanate coating layer (3nm thick), a carbon coating layer (5nm thick) and a polyaniline coating layer (4nm thick) sequentially coated on the surface of the silicon oxygen negative electrode material core from the inside to the outside.

[0060] Example 3 This embodiment provides a method for preparing a negative electrode material for a battery, which is different from Embodiment 1 only in that: in step (1), 0.1 g of tetrabutyl titanate is added.

[0061] The obtained battery negative electrode material includes a silicon oxygen negative electrode material core, and a titanium dioxide coating layer (5nm thick), a lithium titanate coating layer (3nm thick), a carbon coating layer (5nm thick) and a polyaniline coating layer (4nm thick) sequentially coated on the surface of the silicon oxygen negative electrode material core from the inside to the outside.

[0062] Comparative Example 1 This embodiment provides a battery negative electrode material, namely, a silicon-oxygen negative electrode material.

[0063] Comparative Example 2 This comparative example provides a method for preparing a negative electrode material for a battery, which differs from Example 1 only in that a carbon coating layer is first coated on the surface of the silicon-oxygen negative electrode material, and then a titanium dioxide coating layer, a lithium titanate coating layer and a polyaniline coating layer are coated. Specifically, the method comprises the following steps: (1) 10 g of silicon oxide negative electrode material was added to 200 g of tetrahydrofuran, stirred, and dried at 100 °C. The mixture was then placed in a horizontal tube furnace and heated to 600 °C at a heating rate of 5 °C / min under an argon gas flow. The mixture was heated at 600 °C for 2 h to form a carbon coating layer on the surface of the silicon oxide negative electrode material to obtain composite A.

[0064] (2) The obtained composite A was dispersed in 400 mL of anhydrous ethanol, and 0.3 g of tetrabutyl titanate and 20 mL of deionized water were added. After stirring for 20 min, the tetrabutyl titanate generated titanium dioxide and coated on the surface of composite A. Then, 10 mL of lithium nitrate solution (containing 0.1 g of lithium nitrate) was added. After mixing evenly, the mixture was heated and stirred in a water bath at 80 ° C for 20 h. After drying, the mixture was heated to 700 ° C in a nitrogen atmosphere and kept warm for 3 h to convert the surface layer of titanium dioxide into lithium titanate to obtain composite B.

[0065] (3) 10 g of the complex B was added to 200 mL of anhydrous ethanol and magnetically stirred for 10 minutes. At a temperature of 80°C, 0.5 g of 3-aminopropyltriethoxysilane was added. After reacting for 1.5 hours, 2 mL of aniline was added and stirred to obtain a mixed solution A. 0.3 g of ammonium persulfate was dissolved in 10 mL of deionized water to obtain an ammonium persulfate solution. The obtained ammonium persulfate solution was slowly added dropwise to the mixed solution A through a separatory funnel and reacted for 3 hours. After the reaction was completed, the mixture was repeatedly washed with deionized water and ethanol and filtered twice, and then placed in a vacuum environment at 100°C until completely dried to obtain a battery negative electrode material. The battery negative electrode material includes a silicon oxygen negative electrode material core, and a carbon coating layer, a titanium dioxide coating layer, a lithium titanate coating layer and a polyaniline coating layer sequentially coated on the surface of the silicon oxygen negative electrode material core from the inside to the outside.

[0066] Comparative Example 3 This comparative example provides a method for preparing a negative electrode material for a battery, which differs from Example 1 only in that: In step (3), an ion conductor polymer (specifically, a three-stage copolymer of lithium styrene sulfonate, eugenol and caprolactone) is coated on the surface of the second composite.

[0067] The obtained battery negative electrode material includes a silicon oxygen negative electrode material core, and a titanium dioxide coating layer, a lithium titanate coating layer, a carbon coating layer and a lithium styrene sulfonate-eugenol-caprolactone three-stage copolymer conductive polymer coating layer which are sequentially coated on the surface of the silicon oxygen negative electrode material core from the inside to the outside.

[0068] Comparative Example 4 This comparative example provides a method for preparing a negative electrode material for a battery, which differs from Example 1 only in that no lithium titanate coating layer is applied, i.e., 10 mL of lithium nitrate solution (containing 0.1 g of lithium nitrate) is not added in step (1).

[0069] The obtained battery negative electrode material comprises a silicon oxygen negative electrode material core, and a titanium dioxide coating layer, a carbon coating layer and a polyaniline coating layer which are sequentially coated on the surface of the silicon oxygen negative electrode material core from the inside to the outside.

[0070] test: (1) The X-ray diffraction pattern of the negative electrode material of the battery in Example 1 is as follows: Figure 2 As shown, because the titanium dioxide coating layer and the lithium titanate coating layer are very thin, there are no obvious diffraction peaks of titanium dioxide and lithium titanate.

[0071] (2) The X-ray photoelectron spectrum of the negative electrode material of the battery in Example 2 is as follows: Figure 3 As shown, the results indicate the successful coating of TiO2.

[0072] (3) The energy spectrum of the negative electrode material of the battery in Example 3 is as follows: Figure 4As shown, it can be seen that Ti, O and C elements are uniformly coated on the surface of the silicon-oxygen negative electrode material.

[0073] (4) The battery negative electrode materials in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are all prepared into lithium ion batteries (the difference between the lithium ion batteries is only that the negative electrode materials are the battery negative electrode materials in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively), and cycle tests and rate tests are carried out under the same conditions.

[0074] The cycle test results of the lithium ion batteries prepared using the battery negative electrode materials in Example 1 and Comparative Example 1 are as follows: Figure 5 As shown, it can be seen that the capacity retention rate of the lithium ion battery prepared by using the battery negative electrode material in Example 1 after 100 cycles is 86.6%, while the capacity retention rate of the lithium ion battery prepared by using the battery negative electrode material in Comparative Example 1 after 100 cycles is only 52.1%.

[0075] The cycle test results of the lithium ion batteries prepared using the battery negative electrode materials in Example 2 and Comparative Example 2 are as follows: Figure 6 As shown, it can be seen that the capacity retention rate of the lithium ion battery prepared by using the battery negative electrode material in Example 2 after 100 cycles is 85.0%, while the capacity retention rate of the lithium ion battery prepared by using the battery negative electrode material in Comparative Example 2 after 100 cycles is only 58.3%.

[0076] The cycle test results of the lithium ion batteries prepared using the battery negative electrode materials in Example 3 and Comparative Example 3 are as follows: Figure 7 As shown, it can be seen that the capacity retention rate of the lithium ion battery prepared by using the battery negative electrode material in Example 3 after 100 cycles is 80.6%, while the capacity retention rate of the lithium ion battery prepared by using the battery negative electrode material in Comparative Example 3 after 100 cycles is only 58.8%.

[0077] In addition, if Figure 8 As shown, the capacity retention rate of the lithium ion battery prepared by using the battery negative electrode material in Comparative Example 4 after 100 cycles is 54.1%, which is significantly worse than the cycle performance of the lithium ion battery prepared by using the battery negative electrode material in Example 1, Example 2 and Example 3.

[0078] This shows that the use of inorganic-carbon layer-organic coating can significantly improve the battery's cycle capacity retention rate and first cycle coulombic efficiency. This improvement is mainly attributed to the role of the four coating layers, which effectively reduce the occurrence of naturally formed SEI films and side reactions in the battery.

[0079] The rate test results of lithium ion batteries prepared using the battery negative electrode materials in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are as follows: Fig. 9 As shown (wherein 0.1C, 0.3C, 0.5C, etc. refer to the discharge rate. If the rated capacity of the battery is 500mAh, then when discharging at a discharge rate of 0.1C, the current used is 50mA), compared with the battery negative electrode materials in Comparative Examples 1, 2 and 3, the lithium ion battery prepared using the battery negative electrode material in Example 1 has better rate performance.

[0080] (5) The impedance diagrams of the lithium-ion batteries made with the negative electrode materials of Example 2 and Comparative Example 1 after 0.5 and 50.5 cycles are shown in Figure 2. Fig.10 As shown (where Z′ represents the real part of the impedance value, and Z″ represents the imaginary part of the impedance value), it can be seen that the coating layer helps to enhance the overall conductivity of the coating material, thereby improving the charge and discharge performance of the battery.

[0081] In summary, the present invention provides a battery negative electrode material and a preparation method thereof. The titanium dioxide coating layer in the present invention has a certain rigidity, which can buffer the volume expansion of the silicon-based negative electrode material during the lithiation process, reduce the mechanical stress of the silicon-based negative electrode material, and enhance the structural stability. The lithium titanate coating layer can be used as a lithium ion conductive layer to enhance the transmission of lithium ions. It can also act as an artificial SEI film to avoid the natural generation of the SEI film during the cycle. On the one hand, the carbon coating layer can enhance the conductivity of the silicon-based negative electrode material, and on the other hand, it also has a certain buffering effect on the volume expansion of the silicon-based negative electrode material. The polymer coating layer has good toughness and conductivity, which can effectively alleviate the volume expansion of the silicon-based negative electrode material and prevent the silicon-based negative electrode material from breaking. In addition, it can not only act as an intermediate isolation layer between the active material (i.e., the silicon-based negative electrode material) and the electrolyte, reduce the occurrence of side reactions, and be more friendly to the electrolyte, but also promote interface ion diffusion, thereby ensuring the smooth embedding and de-embedding of lithium ions. Under the action of these four coating layers, the integrity of the silicon-based negative electrode material can be maintained, avoiding direct contact between the silicon-based negative electrode material and the electrolyte, reducing the occurrence of side reactions, reducing the capacity attenuation of the battery during the charge and discharge cycle, and improving the battery's rate performance and cycle stability.

[0082] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A battery negative electrode material, characterized in that: The battery negative electrode material comprises a core, a titanium dioxide coating layer coated on the surface of the core, a lithium titanate coating layer coated on the surface of the titanium dioxide coating layer, a carbon coating layer coated on the surface of the lithium titanate coating layer, and a polymer coating layer coated on the surface of the carbon coating layer; The inner core comprises a silicon-based negative electrode material; and the polymer coating layer comprises at least one of polyaniline, polythiophene and polypyrrole.

2. The battery negative electrode material according to claim 1, characterized in that: The silicon-based negative electrode material includes at least one of a silicon negative electrode material, a silicon-oxygen negative electrode material and a silicon-carbon negative electrode material.

3. The battery negative electrode material according to claim 2, characterized in that: The particle size of the silicon-based negative electrode material is 0.1-50 μm; The thickness of the titanium dioxide coating layer is 2-18 nm; the thickness of the lithium titanate coating layer is 2-10 nm; the thickness of the carbon coating layer is 5-10 nm; and the thickness of the polymer coating layer is 2-8 nm.

4. A method for preparing a negative electrode material for a battery according to claim 1, characterized in that: The steps include: Provide silicon-based negative electrode materials; forming a titanium dioxide coating layer on the surface of the silicon-based negative electrode material, and forming a lithium titanate coating layer on the surface of the titanium dioxide coating layer to obtain a first composite; forming a carbon coating layer on the surface of the first composite to obtain a second composite; A polymer coating layer is formed on the surface of the second composite to obtain a battery negative electrode material.

5. The preparation method according to claim 4, characterized in that: The steps of forming a titanium dioxide coating layer on the surface of the silicon-based negative electrode material and forming a lithium titanate coating layer on the surface of the titanium dioxide coating layer to obtain the first composite specifically include: The liquid phase coating method is used to coat titanium dioxide on the surface of the silicon-based negative electrode material; The silicon-based negative electrode material coated with titanium dioxide on the surface is mixed with a lithium source and kept at 500-700° C. for 3-5 hours in an inert atmosphere, so that a titanium dioxide coating layer and a lithium titanate coating layer are sequentially formed on the surface of the silicon-based negative electrode material to obtain a first composite.

6. The preparation method according to claim 5, characterized in that: The steps of coating titanium dioxide on the surface of silicon-based negative electrode material by liquid phase coating method specifically include: The silicon-based negative electrode material is added into a first solvent, and then a titanium source and water are added, so that titanium dioxide is coated on the surface of the silicon-based negative electrode material through a hydrolysis reaction.

7. The preparation method according to claim 6, characterized in that: The titanium source includes at least one of titanium tetrachloride, tetrabutyl titanate, titanium isopropoxide, titanium sulfate, titanyl sulfate and titanium trichloride; The lithium source includes at least one of lithium nitrate, lithium acetate, lithium phosphate, lithium sulfate, lithium chloride, lithium bromide and lithium iodide.

8. The preparation method according to claim 4, characterized in that: The step of forming a carbon coating layer on the surface of the first composite to obtain the second composite specifically comprises: The first composite is mixed with a carbon source, and heated at 500-700° C. for 2-3 hours under an inert gas atmosphere to form a carbon coating layer on the surface of the first composite, thereby obtaining a second composite.

9. The preparation method according to claim 8, characterized in that: The carbon source includes at least one of tetrahydrofuran, asphalt, acetone, citric acid and phenolic resin.

10. The preparation method according to claim 4, characterized in that: The step of forming a polymer coating layer on the surface of the second composite to obtain a negative electrode material for a battery specifically comprises: Adding the second complex, polymer monomers, coupling agent and initiator into the second solvent, and after reaction, forming a polymer coating layer on the surface of the second complex to obtain a battery negative electrode material; The polymer monomer includes at least one of aniline, thiophene and pyrrole.

Citation Information

Patent Citations

  • Silicon-based negative electrode material with multi-buffer structure, and preparation method thereof

    CN107623104A

  • Preparation method of composite negative electrode material of lithium ion battery

    CN108365194A

  • Spherical lithium ion battery surface coating material and preparation method thereof

    CN111916718A

  • Large cylindrical lithium ion power battery negative electrode material and preparation method thereof

    CN115440967A

  • Double-shell silicon-carbon composite material, preparation method thereof and lithium ion battery

    CN118507668A

Cited By

  • High-specific-volume and high-rate-performance battery negative electrode material and preparation method thereof

    CN121123233A